Angiotensin-(1–7) as a Potential Therapeutic Strategy for Delayed Cerebral Ischemia in Subarachnoid Hemorrhage - Annoni, Filippo; Moro, Federico; Caruso, Enrico; Zoerle, Tommaso; Taccone, Fabio Silvio; Zanier, Elisa R. (Frontiers in Immunology, 2022)
Aneurysmal subarachnoid hemorrhage (SAH) is relevant cause of mortality and morbidity worldwide; moreover, survivors to the initial hemorrhage are often exposed to secondary brain injuries and the development of delayed cerebral ischemia, further increasing the risk of poor outcome. In recent years, the renin-angiotensin system (RAS) has been proposed as a target pathway for therapeutic interventions after brain injury. The RAS is a complex system of biochemical reaction critical for the modulation of several systemic functions, including inflammation, vascular tone, endothelial activation, water balance, fibrosis, and apoptosis. The RAS system is classically divided into a pro-inflammatory axis, mediated by Angiotensin II and its specific receptor AT1R, and a counterbalancing system, represented in humans by Angiotensin (1-7) (Ang-(1-7)) and its receptor, MasR. Experimental data suggest that the upregulation of the Ang-(1-7)/MasR axis could be neuroprotective in multiple pathological conditions including ischemic stroke, cognitive disorders, Parkinson's disease, and depression. In the context of SAH, Ang-(1-7)/MasR neuroprotective and modulating properties could help in reducing brain damage by modulating neuroinflammation, and by direct vascular and anti-thrombotic effects. Here, we review the role of RAS in brain ischemia with a specific focus on SAH and the therapeutic potential of Ang-(1-7) administration.